Conflicto socioambiental y consulta popular en Colombia, 2013–2017. Issue 3 (1st December 2019) - Rodríguez Rodríguez, Angélica; Guzmán Mendoza, Carlos Enrique
Abstract : Full article is in Spanish. English abstract: This article analyses how, during the period from 2013 to 2017, popular consultation was used by nine Colombian municipalities to slow mining and hydrocarbon exploitation due to their harmful socio-environmental impact. In order to do so, we review the concept of sustainable development in relation with the legal mechanisms employed to its promotion and defense. We present the developments of the extractive sector in Colombia and discuss the nine popular consultations promoted by the municipal authorities. We conclude that despite the suitability of popular consultation, it has proved to be ineffective to stop the extractive projects that generate harmful effects on the communities where they are developed. Spanish abstract: Este artículo analiza cómo, durante el periodo 2013–2017, la consulta popular fue utilizada por nueve municipios colombianos para frenar la explotación minera y de hidrocarburos dado su dañino impacto socioambiental. Para ello, revisamos el concepto de desarrollo sostenible en relación con los mecanismos legales empleados para su promoción y defensa. Presentamos los desarrollos del sector extractivo en Colombia y discutimos las nueve consultas populares adelantadas por los entes municipales. Concluimos que, a pesar de su idoneidad, la consulta popular ha resultado poco efectiva para detener los proyectos extractivos que generan efectos nocivos sobre las comunidades donde se desarrollan. French abstract: Cet article analyse comment, au cours de la période 2013-2017, une consultation populaire a été menée dans neuf municipalités colombiennes sur l'exploitation minière et des hydrocarbures, en lien avec leur impact socio-environnemental. Pour ce faire, nous procédons d'abord à une révision du concept de développement durable par rapport aux mécanismes juridiques utilisés pour sa promotion et sa défense. Nous présentons ensuite les développements du secteur extractif en Colombie et analysons les neuf consultations menées par les autorités municipales. Finalement, nous concluons que, malgré son utilité, la consultation populaire s'est révélée inefficace pour mettre un terme aux projets d'extraction là où ils ont eu des effets néfastes sur les communautés.